Nasal rustle: The retrospective and prospective investigation of effects of bubbling of secretions on speech. (January 2021) - Hosseinabad, Hedieh Hashemi; Kummer, Ann W.; Boyce, Suzanne
Abstract: Objective: "Nasal rustle" is a type of nasal emission associated with a small velopharyngeal (VP) gap and distracting loud noise. Currently, the mechanisms behind noise generation are unclear. In this study, we use a combination of retrospective and prospective data to test the hypotheses that bubbling of secretions could be a source of audible noise. Design: Retrospective: Nasopharyngoscopy records of 151 patients with nasal rustle were reviewed to determine if bubbling occurred during their nasopharyngoscopy examination. Prospective: Nine children with nasal rustle and bubbling of secretions were suctioned with the scope in place to assure removal of secretions. The Nasometer II was used to record the children's production of oral sentences prior to and post suctioning. All sentences were analyzed for the presence or absence of noise, nasalance scores, and Cepstral Peak Prominence (CPP). Intra-and inter-judge reliability of coding was high. Results: Retrospective: 70% of the patients with nasal rustle had bubbling of secretions during nasopharyngoscopy. Prospective: Percentages of audible noise were reduced significantly post suctioning (Friedman's Test, Chi-square = 24.5, p = 0.001) with the greatest decrease in syllables with fricatives and bilabial stops (p < 0.05). The average CPP and nasalance scores pre-vs post-suctioning showed no significant differences (p = 0.91, 0.29). Conclusions: Retrospective: The high percentage of patients with nasal rustle had bubbling of secretions when producing speech in nasopharyngoscopy evaluations. Prospective: The incidence of audible noise was reduced as a result of suctioning. This suggests that the presence of secretions contributes to the production of nasal rustle.